2014
DOI: 10.2478/intag-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Compression loading behaviour of sunflower seeds and kernels

Abstract: A b s t r a c t. The present study was carried out to investigate the compression loading behaviour of five Indian sunflower varieties (NIRMAL-196, NIRMAL-303, CO-2, KBSH-41, and PSH-996) under four different moisture levels (6-18% d.b). The initial cracking force, mean rupture force, and rupture energy were measured as a function of moisture content. The observed results showed that the initial cracking force decreased linearly with an increase in moisture content for all varieties. The mean rupture force als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Higher values of the pea seed moisture content caused a decrease the modulus elasticity of the seed tested (Kaifas, 1984). The same dependence was obtained for wheat seeds by Babić et al (2011), corn seeds by Babić et al (2012), and for sunflower seeds by Selvam et al (2014).…”
Section: Introductionsupporting
confidence: 80%
“…Higher values of the pea seed moisture content caused a decrease the modulus elasticity of the seed tested (Kaifas, 1984). The same dependence was obtained for wheat seeds by Babić et al (2011), corn seeds by Babić et al (2012), and for sunflower seeds by Selvam et al (2014).…”
Section: Introductionsupporting
confidence: 80%
“…Hence, unlike the matured coconuts, the presence of high moisture in the tender coconut husk may facilitate easy punching. Similarly, Selvam, Manikantan, Chand, Sharma, and Seerangurayar () also reported that the interaction of variety and moisture content has a significant effect on rupture force and initial cracking force for sunflower kernel and seed.…”
Section: Resultsmentioning
confidence: 83%
“…Five hundred grams corn kernels, 100 g corn cobs, 50 g corn stalks and 50 g corn husks were randomly selected from the mixture as a group of samples to determine the moisture contents. Samples were prepared in triplicate and were dried in a DZF-6050 thermostatic drying oven (Rongshida Electric Equipment Co., Ltd., Kunshan, China) at 105 ± 1 • C for 24 h [29]. The moisture contents of kernels, cobs, stalks, hulks, and stigma, measured on a wet basis method, were 24.8 ± 0.19%, 54.5 ± 0.22%, 68.3 ± 0.15%, 26.6 ± 0.17%, and 25.7 ± 0.11%, respectively.…”
Section: Physical Properties Of Componentsmentioning
confidence: 99%